New Mode of Online Shop Fraud at Shopee and Solving Problems through Business Regulations - Aprinawati; Rina Handayani; Asma Nadya Nasution; Debby Ayu Andrera; Muhammad Dzaki Zulwaqar; Roma Yana Sitanggang (Jurnal Ekonomi dan Bisnis Digital, 2023)
In the current digital era, we have activities that are completely online, one of which is the Online Shop activity. This research was conducted to examine a new mode of online shop fraud at Shopee and provide a solution to this problem. This research uses a descriptive research method (qualitative). As well as using a statutory approach and a conceptual approach. The data collection method is carried out by obtaining various sources of information from literature and visual literacy. The results of the study show that the new mode of online store fraud at Shopee is in the form of baiting Shopee balance top-ups and asking for consumer fund pin numbers, which will drain the consumer's finances.